A proposal to develop the performance of the educational supervisor in practical education in the faculties of education in Palestine according to the modern evaluation criteria - Al Awadi, Raafat (Arab Journal for Sciences and Research Publishing, 2017)
The study aimed to reveal the performance of the educational supervisor in practical education in the faculties of education in Palestine to the standards of modern evaluation from the point of view of students, and then develop a proposed proposed perception, and the study used the descriptive analytical curriculum, and the sample of the study consisted of (189) students, selected in a class way Relative randomness from al-Azhar and Al-Aqsa Universities in Gaza, the questionnaire applied in the second semester 2015/2016. The results revealed that the reality of the educational supervisor performed in practical education in the faculties of education in Palestine to the standards of modern evaluation from the point of view of students came to a high degree with a relative weight of (78.13%), and the focus of the standards of the use of educational means received the highest relative weight of (81.3%), and then the axis of standards During the course of the study, a relative weight of (79.4%), then the axis of pre-teaching criteria with a relative weight of (78.0%), then the axis of criteria after the lesson (evaluation), and received a relative weight of (77.1%) and the relative weight of the axis of personal criteria (74.8%) and the results revealed no statistically significant differences in the progression The members of the sample of the study saw the reality of the performance of the educational supervisor in practical education in the faculties of education in Palestine for the modern evaluation criteria due to variables: university, cumulative rate, sex. The results were interpreted in the light of the literature of the study, and the study provided the proposed scenario.